SOCIAL MEDIA MARKETING AND BRAND LOYALTY AT SAFARICOM COMPANY, KENYA - Glendah, Sindani Tsimbiri; Alala, Dr. Ondiek B.; Dishon, Mr.Wanjere (European Journal of Business and Strategic Management, 2019)
Purpose: Social marketing is the design, implementation and control of programs calculated to influence the suitability of social ideas. It has been generally agreeable from many studies in the recent past that companies that have used social media marketing exhibit high brand loyalty and undoubtedly is an important aspect of organizational success. This study purposed to analyze and investigate on how cocreation affect loyalty of customers towards Safaricom Ltd Company. This study objective was to assess the effect of co creation on brand loyalty. The study population was eighty three employees of Safaricom Limited Company. Methodology: The study employed stratified sampling technique and simple random sampling. The sample size was twenty five respondents. The study collected primary data using open and closed ended questionnaires. The data was organized, presented, analyzed and interpreted using descriptive statistics, the frequencies, percentages, and charts. Findings: The findings concluded that social media marketing has a strong and positive influence on brand loyalty. The study concluded that social media marketing as a tool of the company has increased sales volume and the market share of the company. Unique contribution to Theory, Practice and Policy: The study recommends that top management should be involved in the continuous evaluation and monitoring of social media, marketing tools to ensure that the goals and objectives set are achieved and appropriate corrective actions are taken in the event of deficiencies.